Investigation of markers of allergic sensitization and viral infections in children with allergy and asthma - Dubakienė, Rūta; Rubinaitė, Vilija; Petronytė, Malvina; Dalgėdienė, Indrė; Rudzevičienė, Odilija; Dubakaitė, Dalia; Rudalevičienė, Palmira; Žvirblienė, Aurelija (Acta medica Lituanica, 2017)
Background. Allergic diseases are the most prevalent chronic diseases in the developed countries. It is believed that early allergic sensitization and respiratory viral infections play an important role in the development of allergic diseases and asthma. Methods. The current study investigated the correlation between asthma, allergy, and various markers – allergen-specific IgE, IgG4 and IgA, ECP, IgM, and IgG antibodies against respiratory viruses hRSV and hPIV1-4 – in blood serum samples from 80 children (mean age 5.2 years) recruited from the Lithuanian birth cohort. Children were divided into three groups according to their diagnosis: asthma (n = 25), allergy without asthma (n = 14), and control group (n = 41). Results. Based on retrospective data, airway infections and bronchitis by the age of two years were associated with asthma in later childhood. The presence of IgM and IgG antibodies against hRSV and hPIV1–4 at the age of five years were not associated with asthma and allergy: a high rate of persistent or past respiratory viral infections was revealed in all three groups. Among allergic children, increased levels of allergen-specific IgE and d1-specific IgG4 were determined. Conclusion. The current study provides new insights into the relationships between allergic sensitization and respiratory virus infections in children.
Keywords: allergy markers; human respiratory viruses; asthma; allergy; birth cohort